Dual burden of infectious and chronic disease in low-resource U.S. communities: examining relationships between infection, adiposity, and inflammation - Theresa E. Gildner; Samuel S. Urlacher; Katherine L. Nemeth; Jade A. Beauregard; Marcela Pfaff Nash; Angela Zhang; Sophie Waimon; Tara J. Cepon-Robins (Annals of Human Biology)
Background Rising global obesity rates are linked with inflammation and associated morbidities. These negative outcomes are generally more common in low-resource communities within high-income countries; however, it is unclear how frequent infectious disease exposures in these settings may influence the relationship between adiposity and inflammation.Aim We test associations between adiposity measures and distinct forms of inflammation among adults (n = 80) living in low-resource U.S. communities experiencing high levels of obesity and pathogen exposure.Subjects and methods Adiposity measures included BMI and percent body fat. Inflammation measures included systemic inflammation (C-reactive protein [CRP]) and localised intestinal inflammation (faecal calprotectin [FC]). The relationship between a condition characterised by elevated inflammation (Helicobacter pylori infection) and adiposity was also considered.Results Adiposity was not significantly related to FC concentration. However, both adiposity measures were positively related with odds of CRP elevation and H. pylori infection was associated with significantly lower adiposity measures (all p < 0.05).Conclusion For this disadvantaged U.S. sample, the association between adiposity and inflammation varies by the systemic/localised nature of inflammation and the likely underlying cause of inflammation. Defining these associations will improve understanding of how rising obesity rates shape long-term health inequities, with implications for more effective intervention design.